PENGARUH MOTIVASI KERJA, KOMITMEN ORGANISASIONAL DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI KONTRAK - Kusumalita, Gede Nanda; Satrya, I Gusti Bagus Honor (E-Jurnal Manajemen; Vol 8 No 7 (2019)DO - 10.24843/EJMUNUD.2019.v08.i07.p25, 2019)
The purpose of this study was to determine the motivation of contract employees the role of transformational leadership style on contract employees and organizational commitment of contract employees to the performance at pt. Bank rakyat indonesia denpasar regional office. The method of determining the sample in this study uses the census method, where respondents numbered 54 contract employees who worked in the indonesian people's bank denpasar regional office. The data analysis technique used for this study is multiple linear regression. From the results of the analysis of this study indicate that contract employee work motivation has a positive and significant effect on the performance of contract employees. Transformational leadership has a positive and significant effect on contract employee performance. Furthermore, organizational commitment has a positive and significant effect on the performance of contract employees. Suggestions for the bank rakyat indonesia denpasar regional office should pay attention to continuance commitment to be able to improve the performance of contract employees in order to achieve the organization's long-term goals. Keywords : motivation, organizational commitment, transformational leadership, performance, contract employees